2011
DOI: 10.1016/j.reactfunctpolym.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Topology of octaarginines (R8) or IRQ ligand on liposomes affects the contribution of macropinocytosis- and caveolae-mediated cellular uptake

Abstract: It was recently reported that liposomes modified with octaarginine (R8) and its analogue peptide (IRQRRRR: IRQ) are taken into NIH3T3 cells by unique pathways, macropinocytosis and caveolae-mediated endocytosis, respectively. This study evaluated the topology of these peptides as it relates to the uptake routes of liposomes, where they are modified either directly on the surface, or on the edge of a polyethylene glycol (PEG) spacer. The uptake mechanism of peptide-modified liposomes and peptide-modified PEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…A recent study reported that the cellular uptake pathway of R8 modified LP also depends on the position of R8 i.e. whether it is on the surface of the lipid membrane of LP or on the top of the PEG [43]. The RGD modified PEG-LP (RGD-PEG-LP) is taken up mainly by caveolae-mediated endocytosis, which is consistent with findings reported by other research groups [36,44].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study reported that the cellular uptake pathway of R8 modified LP also depends on the position of R8 i.e. whether it is on the surface of the lipid membrane of LP or on the top of the PEG [43]. The RGD modified PEG-LP (RGD-PEG-LP) is taken up mainly by caveolae-mediated endocytosis, which is consistent with findings reported by other research groups [36,44].…”
Section: Discussionsupporting
confidence: 88%
“… 7 , 8 CPPs, 9 small molecular transporters with the capabilities of cell penetration, internalization, and endosomal escape, due to the presence of large number of positively charged arginine residues in acidic environment, have the potential to be useful in drug delivery system. 10 , 11 However, poor specificity for cells is one of the drawbacks of CPPs. 12 By utilizing the function of hydration shell of PEG and acid sensitivity of hydrazone bond, we synthesized a kind of CPPL 13 to improve the selectivity of these peptides for tumor targeting.…”
Section: Introductionmentioning
confidence: 99%